The Hierarchical System of Speech Acts - Kiklewicz, Aleksander (Lingua Posnaniensis, 2011)
The author discusses the problem of speech acts classification on the basis of the pragmatic function. The relevant elements of context, on the example control of the announcement directly to target addressee or to third parties, are also taken into account. The classification of speech acts proposed by the author has a dichotomous as well as a hierarchical character. The author distinguishes and describes the following types of speech acts: inventional vs. conventional; communicative vs. uncommunicative; polite vs. customary; representative vs. performative; expositive vs. verdictive; causative vs. deliberative; descriptive vs. declarative; directive vs. commissive; initiative vs. reactive; extentional vs. intentional; appellative vs. creative; cooperative vs. magic.